Characterization of instrumentation and calibrators for quantitative microfluorometry for immunofluorescence tests. - Kaplan, D S (1989)
The current method for measuring reagents for immunofluorescence microscopy involves a subjective evaluation of the endpoint (titer) with a negative or positive (1+ to 4+) scale. Variability is due to the biological constituents of the reagent, the observer, and the instrumentation. To have reliable methods for evaluation of performance of these products, we are developing a quantitative method that uses photometric measurements of microscopically observed epifluorescence of slide preparations. A computer-controlled microscope-photometer converts the light intensity into a voltage measurement. Our goal is to replace the subjective endpoint determination with an objective, quantitative method. The instrumentation and its operating characteristics are presented in this paper. Selected commercially available fluorescent materials were evaluated as calibrators for the instrumentation. These materials showed consistency in measurement and thus demonstrated their suitability for various levels of calibration. It is possible that they will prove useful as a reference standard for interlaboratory comparisons.